2021
DOI: 10.14238/sp22.6.2021.364-70
|View full text |Cite
|
Sign up to set email alerts
|

Profil Klinis dan Faktor Risiko Mortalitas pada Anak dengan Hidrosefalus di RSUD dr. Soetomo Surabaya

Abstract: Latar belakang. Hidrosefalus merupakan kelainan sistem saraf pusat yang paling umum terjadi baik pada bayi, anak, maupun remaja dan dapat menyebabkan konsekuensi serius berupa mortalitas. Informasi yang menyediakan faktor risiko mortalitas pada anak dengan hidrosefalus masih sangat terbatas.Tujuan. Mengevaluasi dan mengidentifikasi faktor risiko yang berhubungan dengan terjadinya mortalitas pada anak dengan hidrosefalus.Metode. Penelitian analitik observasional pada 89 pasien anak yang menderita hidrosefalus d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Based on data from RSUD dr. Soetomo Surabaya from January 2014 to September 2016 it was reported that 17.97% of pediatric hydrocephalus patients experienced mortality. [3] Hydrocephalus is a clinical condition that can be prevented by modifying risk factors such as meningitis vaccination and good antenatal care, especially in cases of pediatric hydrocephalus. [4] The most common surgical intervention that has become the standard treatment strategy for hydrocephalus in the last few decades is the installation of a ventriculoperitoneal shunt (VP-Shunt).…”
Section: Introductionmentioning
confidence: 99%
“…Based on data from RSUD dr. Soetomo Surabaya from January 2014 to September 2016 it was reported that 17.97% of pediatric hydrocephalus patients experienced mortality. [3] Hydrocephalus is a clinical condition that can be prevented by modifying risk factors such as meningitis vaccination and good antenatal care, especially in cases of pediatric hydrocephalus. [4] The most common surgical intervention that has become the standard treatment strategy for hydrocephalus in the last few decades is the installation of a ventriculoperitoneal shunt (VP-Shunt).…”
Section: Introductionmentioning
confidence: 99%